Engaging Paulo Freire's Pedagogy of Possibility : From Blind to Transformative Optimism. - Rossatto, César Augusto (Rowman & Littlefield Publishers, 2004)
Engaging Paulo Freire's Pedagogy of Possibility is a cross-cultural case study of how people experience schooling in relation to their sense of time and optimism. César Augusto Rossatto examines how real-life situations and social structures influence people's construction of notions of possibilities. The findings of this study suggest that a curriculum based on Freirean critical pedagogy and time theories can be used to enhance time-consciousness values in contemporary social life.